2012
DOI: 10.1002/adsc.201200303
|View full text |Cite
|
Sign up to set email alerts
|

Mild and High‐Yielding Molybdenum(VI) Dichloride Dioxide‐Catalyzed Formation of Mono‐, Di‐, Tri‐, and Tetracarbamates from Alcohols and Aromatic or Aliphatic Isocyanates

Abstract: Both molybdenum(V) dichloride dioxide (MoO 2 Cl 2 ) and its dimethylformamide (DMF) complex catalyze the addition of alcohols to isocyanates giving carbamates. Most additions proceed to completion at room temperature within 20 min using as little as 0.1 mol% of the catalyst when working on a 1-mmol scale or just 100 ppm working on a 20-mmol scale. Sterically encumbered substrates reacted to completion when 1 mol% of the catalyst was employed. Diols, triols, and tetraols reacted with monoisocyanates likewise, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…For this reason, molybdenum-based compounds have found several applications as clean alternatives to heavy metals in the petroleum and plastic industries. In particular, MoCl 2 O 2 , and its related complexes, serve well as Lewis acid catalysts for several organic transformations [ 29 ], ranging from oxidation to acylation, reduction, and carbamylation [ 30 , 31 , 32 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, molybdenum-based compounds have found several applications as clean alternatives to heavy metals in the petroleum and plastic industries. In particular, MoCl 2 O 2 , and its related complexes, serve well as Lewis acid catalysts for several organic transformations [ 29 ], ranging from oxidation to acylation, reduction, and carbamylation [ 30 , 31 , 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…Brückner and coworkers have recently studied catalytic activity of MoCl 2 O 2 and related complexes in the formation of mono-, di-, tri-, and tetracarbamates from a variety of alcohols and isocyanates [ 30 ]. They found that these reactions proceed to completion at room temperature in few minutes using as little as 0.1–1 mol % of the catalyst in chlorinated solvents.…”
Section: Resultsmentioning
confidence: 99%
“…reacting phenols with the general formula 2 with various phenyl isocyanates (3) in the presence of a catalytic amount of 4-dimethylamino pyridine (4-DMAP) in CH 2 Cl 2 or DMF (Scheme 2A). 18,19 However, this reaction did not produce the desired carbamates as no reaction was observed. Therefore, we had to plan an alternative synthetic route.…”
Section: Introductionmentioning
confidence: 99%
“…14 In cases in which isocyanates are involved, in addition to an additional step to prepare the isocyanates, a catalyst and long reaction time are usually needed for the formation of hindered carbamates. 15 The other method is to use dialkyl dicarbonates. Even the most hindered O -tertiary carbamate can be readily prepared using the method.…”
Section: Introductionmentioning
confidence: 99%